The estimated cost of surgically managed isolated traumatic head injury secondary to road traffic accidents - Xinli, You (2018)
Background: Traumatic brain injury secondary to road traffic accidents occurs mainly in the younger age group in which injury related disability leads to long term impact on employment, economic and social consequences across the lifespan. This study was designed to assign a monetary cost (in terms of RM, Ringgit Malaysia) to surgically treated patients in isolated traumatic head injury up to one year post injury. Methods: This costing study consisted of forty-nine patients. Relevant resource items were identified and valued using the direct measurement of costs method, cost accounting methods, standard unit costs method, fees, charges and/or market prices method. These values were than tabulated to generate the total costs for each patients, via a combination of macro-costing and micro-costing methods. Results: The estimated annual cost for all patients was RM 1,471,919.80, with the mean cost per case of RM 30,039.18± 22,986.25 (CI, RM 4089.97-RM 81,007.04). The mean cost of care for per case of mild, moderate and severe head injury was RM 11,041.35± 10,936.88 (CI, RM 4,089.97-RM 33,816.72), RM 32,550± 20,998.76 (CI, RM 10,254.93-RM 69,167.03) and RM 36,917.86± 23,697.34 (CI, RM 4,457.49-RM 81,007.04) respectively. In Univariate Analysis, the following were associated with higher cost of care: severe head injury (P=0.001), sustaining 2 or more intracranial pathologies (P=0.01), having a poor Glasgow Outcome Scale (GOS, 1-3) (P=0.02), tracheostomised (P<0.001) and contracting pneumonia (P<0.001), while Logistic Background: Traumatic brain injury secondary to road traffic accidents occurs mainly in the younger age group in which injury related disability leads to long term impact on employment, economic and social consequences across the lifespan. This study was designed to assign a monetary cost (in terms of RM, Ringgit Malaysia) to surgically treated patients in isolated traumatic head injury up to one year post injury. Methods: This costing study consisted of forty-nine patients. Relevant resource items were identified and valued using the direct measurement of costs method, cost accounting methods, standard unit costs method, fees, charges and/or market prices method. These values were than tabulated to generate the total costs for each patients, via a combination of macro-costing and micro-costing methods. Results: The estimated annual cost for all patients was RM 1,471,919.80, with the mean cost per case of RM 30,039.18± 22,986.25 (CI, RM 4089.97-RM 81,007.04). The mean cost of care for per case of mild, moderate and severe head injury was RM 11,041.35± 10,936.88 (CI, RM 4,089.97-RM 33,816.72), RM 32,550± 20,998.76 (CI, RM 10,254.93-RM 69,167.03) and RM 36,917.86± 23,697.34 (CI, RM 4,457.49-RM 81,007.04) respectively. In Univariate Analysis, the following were associated with higher cost of care: severe head injury (P=0.001), sustaining 2 or more intracranial pathologies (P=0.01), having a poor Glasgow Outcome Scale (GOS, 1-3) (P=0.02), tracheostomised (P<0.001) and contracting pneumonia (P<0.001), while Logistic Regression Analysis revealed that with increasing age, cost of care increases (b=RM591.60, P=0.05). Conclusion: The mean cost of treatment for this group of patients is high when compared to the per capita income of RM 37,900 in 2016. This generated value acts as a baseline cost for future estimation of treatment where adequate fundings should be channeled timely and appropriately to achieve better health care standards.